Velvet Antler Mobilizes Endothelial Progenitor Cells to Promote Angiogenesis and Repair Vascular Endothelial Injury in Rats Following Myocardial Infarction - Li, Yanjun; Wang, Ziwei; Mao, Min; Zhao, Mingjing; Xiao, Xiang; Sun, Weiliang; Guo, Jing; Liu, Chengxiang; Yang, Deshuang; Qiao, Jiajun; Huang, Li; Li, Lin (Frontiers in Physiology, 2019)
Objective: This investigation examined the effect of velvet antler (VA) on endothelial progenitor cells (EPCs) and the associated effects to promote angiogenesis and repair vascular endothelial injury in rats with myocardial infarction (MI). 1. Methods: VA was analyzed by liquid chromatography-mass spectrometry. Male Sprague Dawley rats were randomly divided into 4 groups: sham, MI, VA and VA +DAPT (gamma-secretase inhibitor IX, a specific blocker of the Notch signaling pathway) group. The rats underwent ligation of the left anterior descending coronary artery for the establishment of MI. Sham-operated rats were used as controls. Blood was taken from the orbital plexus on the first and third days after the operation, and all rats were euthanized on the 7th day after surgery. The blood samples were used to detect the contents of circulating endothelial progenitor cells (CEPCs) and vascular endothelial growth factor (VEGF). Echocardiography was used to test the cardiac function. Cardiac tissue was used for immunohistochemistry and electron microscope, and the marginal zone of the MI tissue was used for western blot and reverse transcription-quantitative polymerase chain reaction. Results: The number of basically qualitative metabolites is 445.Among them, there are 74 substances with relative content greater than 0.05%.VA increased the concentration of CEPCs and VEGF in serum, CD133 content and microvessel density (MVD), and protected the morphology of microvascular endothelial cells in the marginal area of MI at seven days post-MI surgery. CEPCs and MVD in the VA +DAPT group were lower than those of VA group.VA increased the protein expressions of Jagged-1, Notch1, NICD and HES1, and the mRNA expressions of Hes1 and Hey2,while some of the effects could be suppressed by DAPT. Conclusion: These results suggest that VA promotes the mobilization of EPCs to promote angiogenesis and repair vascular endothelial cell damage in post-MI rats, and these effects may be due to activation of the Notch signal pathway.